Pengaruh Jenis Pupuk Organik dan Mulsa terhadap Pertumbuhan Tanaman Lidah Buaya (Aloe vera Mill.) - Edi Santosa (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2003)
The objective of this research was to determine source and level of organic matter on growth of Aloe vera Mill Random complete block (RCB) design was applied where two sources of manure i.e. lamb and cow dung and two kinds of mulch i.e. rice husk and sawmill dust were used. The results showed that application of manure significantly increased the plant height and the number of leaf Lamb dung gave better responses than cow dung, here the best level of lamb dung was 1 kg per plant. Effectiveness of manure application was 4 months, afterward need another  application. Mulching did not affect both plant height and number of leaf significantly. Key words: Aloe, Organic manure, Sawmill dust, Rice husk